Playing Football (soccer) under extreme heat conditions - effect of acclimatisation - Ersöz, G.; Kurdak, S. S.; Özgünen, K. T.; Maughan, R. J.; Zeren, C.; Korkmaz, S.; Yazici, Z.; Binnet, M. S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Exercise intensity is an important factor to induce thermal strain, and soccer is a challenge for the players who have to play under extreme heat conditions. Acclimation is an important intervention to improve thermal tolerance and endurance capacity. Purpose: We aimed to evaluate effect of acclimation on sportive performance during a game played under extreme heat conditions Methods: 11 male acclimated soccer players (age 23 +/- 2 y, years;VO2 max 61.8 +/- 1.1 ml.min-1.kg-1) and 10 unacclimated male soccer players (age 21 +/- 1 y, VO2 max 62.3 +/- 1.5 ml.min-1.kg-1) volunteered to participate in this study. Acclimated (A) and unacclimated (UA) teams played separately against a high level competitive local team at the second half of July 2007. Acclimated players played with an ambient temperature and humidity of 35.6 +/- 0.3 oC and 46 +/- 2 % respectively. Temperature and humidity was recorded as 36.0 +/- 0.2 oC and 61 +/- 1 % during the UA match. Match activity was recorded by a global positioning system. Thermosensor pills were used for body core temperature (Tc) measurements. Blood samples taken 4 hours before and immediately after the game to determine hematocrit (Htc), hemoglobin content (Hb), calculate plasma volume loss, and changes of serum electrolytes. Urine analyses performed before the game. ANOVA and paired sample t-test was used to evaluate the level of significance, and p values < 0.05 were accepted as significant. . Results: The highest Tc value recorded during the last ten minutes of the first half and the difference between A and UA groups was not significant (39.0 +/- 0.3 vs 39.51 +/- 0.3oC respectively). Urine specific gravity value of A players (1020 +/- 6) was significantly lower than UA players (1027 +/- 7) (p < 0.05). Pre- and post-match Htc (43.5 +/- 3.3 vs 46.1 +/- 2.5 %) and Hb values (153 +/- 11 vs 154 +/- 12 g/L) were used to calculate % plasma volume change (-4.3 +/- 13 %) for the A players. The plasma volume loss for the UA players was calculated as -4.8 +/- 2.8 % with pre- and post-mach Htc (45.8 +/- 2.6 vs 47.0 +/- 1.3) and Hb (161 +/- 7 vs 166 +/- 9; p<0.05 ) content. Difference of plasma volume loss for A and UA football players was not significant. Post-match serum Na (141 +/- 2 vs 142 +/- 4 mmol/L), K (4.3 +/- 0.3 vs 4.6 +/- 0.4 mmol/L) for A and UA players were not significantly different from each other. The difference of total distance covered by A (8514 +/- 630 m) and UA (8154 +/- 731) players were not significant. Average distance covered by A players during the second half of the game was significantly higher then the UA players (4156 +/- 354 vs 3761 +/- 358 m respectively; p<0.05). Conclusion: Playing football in extreme heat conditions is an important challenge for adjustment of thermal balance. Increased body temperature together with dehydration may reduce exercise capacity. Acclimatisation is an important intervention to reduce heat strain. The increased sportive performance may be interpreted as another beneficial effect of acclimatisation.